Implementation of Citizenship Learning Discussion Method to Improve Student Learningin School Base - Mawarti, Yuke Siti Agustina (International Journal of Students Education, 2024)
Method discussion is method which nature near relate with study solving problems students are given the task of solving problems in groups, or discussed together. The objectives to be achieved in the discussion method include: Students can think democratic, can value difference practice student think in a way in-depth reflection and training to be responsible for one’s opinion. Discussion method is hoping to provide students with many alternative solutions to learning problems problem. Learning is a process of effort carried out by individuals to obtain a new behavioral change as an experience in interaction with the environment.The discussion method is a way of presenting lessons, in which students are faced with aproblem, which can be a statement or question that is problematic to discuss and solved together. Will but, there is problem at the moment discussion method appliedin learning a subject, some students consider it trivial and impressed less interested in studying a field of study, so that it has an impact on the results obtained student. This study is analysis critical to literature (literature) about method discussion learning education citizenship. Education citizenship expected capable turn on return character participant educate which the more to decline going to character which in accordance with values Pancasila.In Increasing student learning motivation is an integral activity that must exist in learning activities. In addition to providing and transferring knowledge, teachers are also tasked with to increase children’s motivation to learn. Education is the responsibility of the state, will but end spear success objective education is Teacher. Teacher can create source power man which superior and own ability which good, increase quality source power man and effort realize ideals nation Indonesia. Teachers are figures who play an important role in the world in both primary and secondary education, teachers are always involved in an activity agenda education, especially education formal. Teacher own not quite enough answer no only in school but also in public. Teacher is a hero sign service whichdedicating himself to school from the beginning to the end of the lesson, this is solely only to educate the community as participants educate in school.